Low-temperature SCR of NOx by NH3 over MnOx/SAPO-34 prepared by two different methods: a comparative study. Issue 8 (18th April 2017) - Yu, Chenglong; Dong, Lifu; Chen, Feng; Liu, Xiaoqing; Huang, Bichun
ABSTRACT: The low-temperature selective catalytic reduction (SCR) of NO x is a promising technology for removing NO x from flue gases. However, the vulnerability of Mn-based catalysts to SO2 and H2 O poisoning makes them unsuitable for industrial application. Herein, catalysts based on the MnO x /SAPO-34 catalysts were prepared by conventional impregnation and an improved molecularly designed dispersion method for use in the low-temperature SCR. The improved molecularly designed catalyst containing 20 wt% of MnO x exhibited high low-temperature NH3 -SCR activity. Nearly 90% of the NO x was converted exclusively to N2 at 160°C using this catalyst. The structure and morphological analyses of the catalyst showed that the amorphous MnO x was well dispersed on the surface of the support. The reasons for the high performance of the catalysts were ascertained using surface N2 adsorption, XPS, H2 -TPR and NH3 -TPD. The results of these analyses indicated that high specific surface area and the redox capability, of the abundant Mn 4+ and Mn 3+ species, coupled with the surface chemisorbed oxygen and strong acid sites had a significant effect on the SCR reaction. In addition, the effects of SO2 and H2 O on activity of the catalysts were also investigated and it was found that the highly dispersed 20 wt% MnO x /SAPO-34 catalyst exhibited better SO2 poisoning resistance than the other impregnated catalysts.